Production of single cell protein: A Review - Balo, Yonas; Amente, Gerema (Journal of Ecobiotechnology, 2023)
The escalating global population has necessitated an augmentation in food production. The augmented demand for protein has instigated the exploration for novel and economical protein supplements in lieu of conventional proteins. Single Cell Protein (SCP) is a viable solution for protein quality, and microorganisms such as algae, yeast, fungi, and bacteria can produce substantial quantities of SCP due to their rapid development rate and significant protein content in their chemical structure. SCP production requires a small land area and can be produced throughout the year in a shorter time frame. In addition to proteins, SCP comprises carbohydrates, nucleic acids, lipids, minerals, vitamins, and several crucial amino acids. SCP has proven to be an effective substitute for more expensive protein sources such as fish and soybean products. The key factors in SCP production are the preference for cost-effective substrates and non-toxic or non-pathogenic microorganisms. SCP can effortlessly replace traditional protein sources in human and animal feed. This review article concentrates on various aspects of SCP, including its production, utilization of different microorganisms, nutritional benefits, and challenges.